5.1.2 Problems 101 to 200

Table 5.3: First order ode

#

ODE

Mathematica

Maple

109

\[ {}x \left (x +y\right ) y^{\prime } = y \left (x -y\right ) \]

110

\[ {}\left (x +2 y\right ) y^{\prime } = y \]

111

\[ {}y^{2} y^{\prime } x = y^{3}+x^{3} \]

112

\[ {}x^{2} y^{\prime } = x y+x^{2} {\mathrm e}^{\frac {y}{x}} \]

113

\[ {}x^{2} y^{\prime } = x y+y^{2} \]

114

\[ {}x y y^{\prime } = x^{2}+3 y^{2} \]

115

\[ {}\left (x^{2}-y^{2}\right ) y^{\prime } = 2 x y \]

116

\[ {}x y y^{\prime } = y^{2}+x \sqrt {4 x^{2}+y^{2}} \]

117

\[ {}x y^{\prime } = y+\sqrt {x^{2}+y^{2}} \]

118

\[ {}y y^{\prime }+x = \sqrt {x^{2}+y^{2}} \]

119

\[ {}x \left (x +y\right ) y^{\prime }+y \left (3 x +y\right ) = 0 \]

120

\[ {}y^{\prime } = \sqrt {x +y+1} \]

121

\[ {}y^{\prime } = \left (y+4 x \right )^{2} \]

122

\[ {}\left (x +y\right ) y^{\prime } = 1 \]

123

\[ {}x^{2} y^{\prime }+2 x y = 5 y^{3} \]

124

\[ {}y^{\prime } y^{2}+2 x y^{3} = 6 x \]

125

\[ {}y^{\prime } = y+y^{3} \]

126

\[ {}x^{2} y^{\prime }+2 x y = 5 y^{4} \]

127

\[ {}x y^{\prime }+6 y = 3 x y^{{4}/{3}} \]

128

\[ {}2 x y^{\prime }+y^{3} {\mathrm e}^{-2 x} = 2 x y \]

129

\[ {}y^{2} \left (x y^{\prime }+y\right ) \sqrt {x^{4}+1} = x \]

130

\[ {}3 y^{\prime } y^{2}+y^{3} = {\mathrm e}^{-x} \]

131

\[ {}3 y^{2} y^{\prime } x = 3 x^{4}+y^{3} \]

132

\[ {}x \,{\mathrm e}^{y} y^{\prime } = 2 \,{\mathrm e}^{y}+2 x^{3} {\mathrm e}^{2 x} \]

133

\[ {}2 x \sin \left (y\right ) \cos \left (y\right ) y^{\prime } = 4 x^{2}+\sin \left (y\right )^{2} \]

134

\[ {}\left ({\mathrm e}^{y}+x \right ) y^{\prime } = x \,{\mathrm e}^{-y}-1 \]

135

\[ {}2 x +3 y+\left (2 y+3 x \right ) y^{\prime } = 0 \]

136

\[ {}4 x -y+\left (6 y-x \right ) y^{\prime } = 0 \]

137

\[ {}3 x^{2}+2 y^{2}+\left (4 x y+6 y^{2}\right ) y^{\prime } = 0 \]

138

\[ {}2 x y^{2}+3 x^{2}+\left (2 x^{2} y+4 y^{3}\right ) y^{\prime } = 0 \]

139

\[ {}x^{3}+\frac {y}{x}+\left (y^{2}+\ln \left (x \right )\right ) y^{\prime } = 0 \]

140

\[ {}1+y \,{\mathrm e}^{x y}+\left (2 y+x \,{\mathrm e}^{x y}\right ) y^{\prime } = 0 \]

141

\[ {}\cos \left (x \right )+\ln \left (y\right )+\left (\frac {x}{y}+{\mathrm e}^{y}\right ) y^{\prime } = 0 \]

142

\[ {}x +\arctan \left (y\right )+\frac {\left (x +y\right ) y^{\prime }}{1+y^{2}} = 0 \]

143

\[ {}3 x^{2} y^{3}+y^{4}+\left (3 y^{2} x^{3}+y^{4}+4 x y^{3}\right ) y^{\prime } = 0 \]

144

\[ {}{\mathrm e}^{x} \sin \left (y\right )+\tan \left (y\right )+\left ({\mathrm e}^{x} \cos \left (y\right )+x \sec \left (y\right )^{2}\right ) y^{\prime } = 0 \]

145

\[ {}\frac {2 x}{y}-\frac {3 y^{2}}{x^{4}}+\left (\frac {2 y}{x^{3}}-\frac {x^{2}}{y^{2}}+\frac {1}{\sqrt {y}}\right ) y^{\prime } = 0 \]

146

\[ {}\frac {2 x^{{5}/{2}}-3 y^{{5}/{3}}}{2 x^{{5}/{2}} y^{{2}/{3}}}+\frac {\left (3 y^{{5}/{3}}-2 x^{{5}/{2}}\right ) y^{\prime }}{3 x^{{3}/{2}} y^{{5}/{3}}} = 0 \]

159

\[ {}y^{\prime } = f \left (a x +b y+c \right ) \]

160

\[ {}y^{\prime }+p \left (x \right ) y = q \left (x \right ) y^{n} \]

161

\[ {}y^{\prime }+p \left (x \right ) y = q \left (x \right ) y \ln \left (y\right ) \]

162

\[ {}x y^{\prime }-4 x^{2} y+2 y \ln \left (y\right ) = 0 \]

163

\[ {}y^{\prime } = \frac {-y+x -1}{x +y+3} \]

164

\[ {}y^{\prime } = \frac {2 y-x +7}{4 x -3 y-18} \]

165

\[ {}y^{\prime } = \sin \left (x -y\right ) \]

166

\[ {}y^{\prime } = -\frac {y \left (-y^{3}+2 x^{3}\right )}{x \left (2 y^{3}-x^{3}\right )} \]

167

\[ {}y^{\prime }+y^{2} = x^{2}+1 \]

168

\[ {}y^{\prime }+2 x y = 1+x^{2}+y^{2} \]

169

\[ {}y = x y^{\prime }-\frac {{y^{\prime }}^{2}}{4} \]

171

\[ {}x^{\prime } = x-x^{2} \]

172

\[ {}x^{\prime } = 10 x-x^{2} \]

173

\[ {}x^{\prime } = 1-x^{2} \]

174

\[ {}x^{\prime } = 9-4 x^{2} \]

175

\[ {}x^{\prime } = 3 x \left (5-x\right ) \]

176

\[ {}x^{\prime } = 3 x \left (5-x\right ) \]

177

\[ {}x^{\prime } = 4 x \left (7-x\right ) \]

178

\[ {}x^{\prime } = 7 x \left (x-13\right ) \]

179

\[ {}x^{3}+3 y-x y^{\prime } = 0 \]

180

\[ {}x y^{2}+3 y^{2}-x^{2} y^{\prime } = 0 \]

181

\[ {}x y+y^{2}-x^{2} y^{\prime } = 0 \]

182

\[ {}2 x y^{3}+{\mathrm e}^{x}+\left (3 x^{2} y^{2}+\sin \left (y\right )\right ) y^{\prime } = 0 \]

183

\[ {}3 y+x^{4} y^{\prime } = 2 x y \]

184

\[ {}2 x y^{2}+x^{2} y^{\prime } = y^{2} \]

185

\[ {}2 x^{2} y+x^{3} y^{\prime } = 1 \]

186

\[ {}x^{2} y^{\prime }+2 x y = y^{2} \]

187

\[ {}x y^{\prime }+2 y = 6 x^{2} \sqrt {y} \]

188

\[ {}y^{\prime } = 1+x^{2}+y^{2}+x^{2} y^{2} \]

189

\[ {}x^{2} y^{\prime } = x y+3 y^{2} \]

190

\[ {}6 x y^{3}+2 y^{4}+\left (9 x^{2} y^{2}+8 x y^{3}\right ) y^{\prime } = 0 \]

191

\[ {}4 x y^{2}+y^{\prime } = 5 y^{2} x^{4} \]

192

\[ {}x^{3} y^{\prime } = x^{2} y-y^{3} \]

193

\[ {}y^{\prime }+3 y = 3 x^{2} {\mathrm e}^{-3 x} \]

194

\[ {}y^{\prime } = y^{2}-2 x y+x^{2} \]

195

\[ {}{\mathrm e}^{x}+y \,{\mathrm e}^{x y}+\left ({\mathrm e}^{y}+x \,{\mathrm e}^{x y}\right ) y^{\prime } = 0 \]

196

\[ {}2 x^{2} y-x^{3} y^{\prime } = y^{3} \]

197

\[ {}3 x^{5} y^{2}+x^{3} y^{\prime } = 2 y^{2} \]

198

\[ {}x y^{\prime }+3 y = \frac {3}{x^{{3}/{2}}} \]

199

\[ {}\left (x^{2}-1\right ) y^{\prime }+\left (x -1\right ) y = 1 \]

200

\[ {}x y^{\prime } = 6 y+12 x^{4} y^{{2}/{3}} \]

201

\[ {}{\mathrm e}^{y}+y \cos \left (x \right )+\left (x \,{\mathrm e}^{y}+\sin \left (x \right )\right ) y^{\prime } = 0 \]

202

\[ {}9 x^{2} y^{2}+x^{{3}/{2}} y^{\prime } = y^{2} \]

203

\[ {}2 y+\left (1+x \right ) y^{\prime } = 3 x +3 \]

204

\[ {}9 \sqrt {x}\, y^{{4}/{3}}-12 x^{{1}/{5}} y^{{3}/{2}}+\left (8 x^{{3}/{2}} y^{{1}/{3}}-15 x^{{6}/{5}} \sqrt {y}\right ) y^{\prime } = 0 \]

205

\[ {}3 y+y^{4} x^{3}+3 x y^{\prime } = 0 \]

206

\[ {}x y^{\prime }+y = 2 \,{\mathrm e}^{2 x} \]

207

\[ {}\left (2 x +1\right ) y^{\prime }+y = \left (2 x +1\right )^{{3}/{2}} \]

208

\[ {}y^{\prime } = \sqrt {x +y} \]

209

\[ {}y^{\prime } = 3 \left (y+7\right ) x^{2} \]

210

\[ {}y^{\prime } = x y^{3}-x y \]

211

\[ {}y^{\prime } = -\frac {3 x^{2}+2 y^{2}}{4 x y} \]

212

\[ {}y^{\prime } = \frac {3 y+x}{-3 x +y} \]

213

\[ {}y^{\prime } = \frac {2 x y+2 x}{x^{2}+1} \]

214

\[ {}y^{\prime } = \frac {\sqrt {y}-y}{\tan \left (x \right )} \]

231

\[ {}y^{\prime }+y^{2} = 0 \]

527

\[ {}y^{\prime } = x^{2}+y^{2} \]

528

\[ {}y^{\prime } = x^{2}+y^{2} \]

529

\[ {}y^{\prime } = x^{2}+y^{2} \]

651

\[ {}y^{\prime } = 2 x +1 \]

652

\[ {}y^{\prime } = \left (x -2\right )^{2} \]

653

\[ {}y^{\prime } = \sqrt {x} \]